Phytochemical Analysis on Matcha Product Content in Gorontalo City - Fitra Nur Aini Idrus; Sunarto Kadir; Moh. Rivai Nakoe (Universitas Muhammadiyah Palu, 2026)
Matcha is known to have a high content of bioactive compounds compared to regular green tea. This is because matcha is consumed in the form of a whole powder, so that all the compounds in tea leaves are also consumed. In Gorontalo City, matcha drinks are becoming more and more popular so KL, NK, and RHU were chosen as the sampling locations because they offer a variety of matcha products. The formulation of the problem in this study is what are the ingredients contained in matcha products in Gorontalo City. This study aims to identify and analyze the content contained in matcha products. This study uses a quantitative descriptive design to determine the content of matcha through phytochemical analysis. The study population included matcha drinks from 25 coffee shops and 8 street coffees in Gorontalo City, with samples taken from KL, RHU, and NK. The results showed that the RHU sample had the highest total phenol content of 209.34 mg GAE/g, followed by NK 184.64 mg GAE/g, and KL 149.30 mg GAE/g. The mean value of IC₅₀ showed that the antioxidant activity of RHU was very strong (34.87 ppm), strong NK (52.41 ppm), and moderate KL (109.32 ppm). In conclusion, KL, NK, and RHU matcha samples in Gorontalo City are still safe to consume based on their phenol content. The antioxidant activity of the KL sample is moderate, NK is strong, and RHU is very strong, it is recommended to consume matcha wisely and business actors need to pay attention to the quality of raw materials and processing processes to maintain the content of active compounds of the product.